Prescribed fire impact on the stability of superficial draining in a pine forest - Urrutia Hernández, Isyoel; Rodríguez Alfaro, Beatriz; González Menéndez, Modesto; Martínez Becerra, Luís Wilfredo; Flores Garnica, José Germán; Alonso Torrens, Yatsunaris (Instituto de Ecología, A.C., 2020)
The following work presents the results obtained by fire management applied in coniferous ecosystems, in the Agroforestry enterprise La Palma, Pinar del Río, Cuba with the purpose of looking for economic and versatile alternatives for forest resources management. Although in Cuba, prescribed burns have few antecedents, this practice is implemented in several countries as a support tool for its integral forestry management plans. Little attention is paid in Cuba to prescribed burns due to the scarce information available about its effects at medium and long terms in forest ecosystems. In this paper, some aspects of prescribed-burns influence such as: definition, application time, fire effects on fuel material, vegetation and superficial glide are analyzed. Results show that prescribed burns can represent a support alternative in integral forestry management because of the reduction of fuel materials and the risk of forest fires; also, they allow to mitigate forest fires effects on surface draining and contribute to pine ecosystems conservation.